EVALUACIÓN DE LOS RIESGOS PSICOSOCIALES Y EL ÁREA EMOCIONAL EN EL PERSONAL MÉDICO DEL HOSPITAL MARTÍN ICAZA DE BABAHOYO - GARCIA MARCILLO ANGIE ANAHIS (2024)
This research aims to analyze the relationship between psychosocial risks and the emotional area in the medical staff of the General Hospital "Martin Icaza" in the city of Babahoyo. Psychosocial risks include a series of factors that can negatively affect the mental health of employees, such as work stress, burnout, anxiety, and depression. Identifying and evaluating these risks is essential to implement preventive and corrective actions that promote a healthier and safer work environment, while the emotional area is the ability to perceive, evaluate, express one's own emotions and generate emotions that help to think and understand the emotions of others. The research was carried out with a population of 206 with a convenience sample of 80 adults, including both men and women, selected through probabilistic sampling. A qualitative approach was utilized, with a non-experimental research design and a correlational methodology. Data were collected through standardized questionnaires, including the FPSICO 3.0 Psychosocial Risk Factors Assessment developed by the Spanish National Institute for Occupational Safety and Health (INSST) and an Emotional Intelligence test validated by Daniel Goleman. The statistical analysis of Pearson's coefficient using the JAMOVI program showed a strong significant positive correlation of R 0.552 *** between the two variables, indicating that psychosocial risks affect the emotional area of health professionals.